Stakeholder Engagement in Decision Making and Pathways of Influence for Southern Ocean Ecosystem Services - Solomonsz, Josh; Melbourne-Thomas, Jess; Constable, Andrew; Trebilco, Rowan; van Putten, Ingrid; Goldsworthy, Lyn (Frontiers in Marine Science, 2021)
Southern Ocean ecosystem management is characterised by a unique and complex international network of stakeholders and stakeholder relationships (a ‘transactional landscape’) relating to the globally significant services that these ecosystems support. This transactional landscape spans governments, industry (fishing and tourism), scientific research, conservation non-government organisations, civil society and international decision-making forums. We used a network approach for stakeholder mapping to provide the first description of the transactional landscape for Southern Ocean ecosystem management – both in terms of the connections between stakeholders and ecosystem services, and directly between stakeholder groups. We considered 65 stakeholders and their relationships to 12 provisioning, regulating, supporting and cultural ecosystem services. An analysis of the connections within this network reveals differences in the degree of connectivity between stakeholders and ecosystem services. Notably, ecosystem science facilitates high connectivity between stakeholders and provisioning services, but there is little connectivity between stakeholders and supporting services. We then applied a formal ‘values-rules-knowledge’ framework to a set of case studies to analyse the decision-making process in relation to Southern Ocean ecosystem services, as well as the relative importance of different stakeholder groups which were considered in the network analysis. Our analyses suggest that emphases for decision making have been on knowledge and rules, but that wider consideration of values across the broader stakeholder landscape – together with science (knowledge) and governance (rules) – might better support decision making for Southern Ocean ecosystem conservation and management, and provide a stronger foundation for sustainable provision of ecosystem services into the future.